Newspapers in Science Communication: A Content Analysis on Science and Technology News - Dönmez, İsmail (My University, 2023)
Science communication describes the connection between science and society in various ways. Written media and media tools contribute to strengthening science communication. The aim of this research was to examine the science and technology news in daily newspapers published in Turkey. Three newspapers in Turkey (Hürriyet, Sabah, and Posta), and their publications between August 28th and September 21st, 2019, were selected in this study. Some reviews have been made into how often these newspapers include science and technology events occurring in Turkey and around the world, what type of scientific news there is, and in what way the socio-scientific contents are presented in newspapers. The content analysis method was used in the study and the news items were presented in categories. As a result of the research, it was observed that science and technology news is given little space in these newspapers and is generally presented in the small columns on the last pages. It was seen that newspapers are an important tool in presenting scientific content and socio-scientific issues to society, but these depictions made are in certain patterns.
Keywords: Media; Content Analysis; Newspapers; Science Communication; Socio-scientific Issues